Monsoon-driven seasonal hypoxia along the northern coast of Oman - DiMarco, Steven F.; Wang, Zhankun; Chapman, Piers; al-Kharusi, Lubna; Belabbassi, Leila; al-Shaqsi, Hilal; Stoessel, Marion; Ingle, Stephanie; Jochens, Ann E.; Howard, Matthew K. (Frontiers in Marine Science, 2023)
Dissolved oxygen and current observations from a cabled ocean observatory in the Sea of Oman show that the annual recurrence of coastal hypoxia, defined as dissolved oxygen concentrations ≤63 μM, is associated with the seasonal cycle of local monsoon winds. The observations represent the first long-term (5+ years) continuous moored observations off the northern Omani coast. During the summer/fall southwest (SW) monsoon season (Jun-Nov), winds in the Sea of Oman generate ocean currents that result in coastal upwelling of subsurface waters with low dissolved oxygen concentrations. The source of the poorly oxygenated water is the oxygen minimum zone (OMZ) in the Arabian Sea, a layer approximately 1000-m thick within the 100 to 1200 m depth range, where dissolved oxygen values approach anoxia. During the winter monsoon season (Dec-Feb), the Sea of Oman winds are from the northwest, forcing strong and persistent southeast currents. These winds generate oceanic downwelling conditions along the coastal ocean that ventilate waters at depth. Possible impacts of the monsoon-driven seasonal hypoxia on local fisheries and implications due to climate change are also discussed in this study.